1993
DOI: 10.1128/jb.175.2.465-473.1993
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis urease: transcriptional regulation by UreR

Abstract: Proteus mirabilis urease catalyzes the hydrolysis of urea, initiating the formation of urinary stones. The enzyme is critical for kidney colonization and the development of acute pyelonephritis. Urease is induced by urea and is not controlled by the nitrogen regulatory system (ntr) or catabolite repression. Purified whole-cell RNA from induced and uninduced cultures of P. mirabilis and Escherichia coli harboring cloned urease sequences was probed with a 4.2-kb BglI fragment from within the urease operon. Autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…Furthermore, Mobley and Chippendale (1990) showed that all P. mirabilis isolated from different clinical source produced a high amount of urease phenotypically compared to other bacteria and there was a concordance between phenotypic and molecular detection of urease activity. In addition, Nicholson et al [28] and Ali and Yousif (2015) found that ureC gene is very abundant in P. mirabilis bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Mobley and Chippendale (1990) showed that all P. mirabilis isolated from different clinical source produced a high amount of urease phenotypically compared to other bacteria and there was a concordance between phenotypic and molecular detection of urease activity. In addition, Nicholson et al [28] and Ali and Yousif (2015) found that ureC gene is very abundant in P. mirabilis bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The urease gene cluster of P. mirabilis contains eight genes, including the urea-dependent transcriptional activator ureR, the enzyme structural genes ureABC, and the four accessory genes ureDEFG (16,28,32). Mutations in structural or accessory genes usually result in a complete loss of catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Urease genes of P. mirabilis have been cloned (15) and sequenced (16,28,32), and deletion mutations have been constructed (10,32). In the course of these studies, we observed that clones lacking ureE, ureF, or ureG (accessory genes in the P. mirabilis urease gene cluster) do not express catalytically active urease in unsupplemented medium.…”
mentioning
confidence: 99%
“…Ammonia is produced by almost all organisms, it is one of the most characteristic odors in fresh manure (Richardson, 1916), and it can attract L. sericata adults (Hilker and Meiners, 2002). Urease catalyzes the hydrolysis of urea into carbon dioxide and ammonia (Nicholson et al, 1993), and in P. mirabilis, urease is encoded by the ure operon that contains eight genes. UreR is the transcription regulator of P. mirabilis urease.…”
Section: Discussionmentioning
confidence: 99%